Hereditary pancreatitis of 3 Chinese children: Case report and literature review. Issue 36 (September 2016) - Dai, Li-Na; Chen, Ying-Wei; Yan, Wei-Hui; Lu, Li-Na; Tao, Yi-Jing; Cai, Wei
Abstract: Background: Hereditary pancreatitis (HP) is quite rare and is distinguished by incomplete penetrance presentation as early-onset relapsing pancreatitis, usually beginning in childhood. HP is now known to be commonly relevant to mutations in the PRSS1 (gene-encoding cationic trypsinogen), SPINK1 (serine protease inhibitor, Kazal type 1), CFTR (cystic fibrosis), carboxypeptidase A1 (CPA1), and chymotrypsin C ( CTRC ) genes as reported in some Caucasian studies. HP has a variable spectrum of severity and may develop complications. Methods & Results: We describe the clinical course of 3 preschool children, hospitalized with postprandial abdominal pain, whose laboratory tests showed high serum amylase. Similar episodes of abdominal pain led to readmission, and the patients recovered quickly after using symptomatic therapy. The condition of the first boy, who developed a pancreatic tail pseudocyst and splenic infarction, was especially complicated. The boy underwent 2 endoscopic retrograde cholangiopancreatographies and stenting, along with a surgical procedure that completely relieved his symptoms for 3 months. The 3 patients and their parents were given genetic testing. All of the patients carried 1 or more gene mutations inherited from their mothers, fathers, or both parents; however, none of the parents were affected. Conclusion: For children with repeated pancreatitis, clinicians should consider HP in the differential diagnosis. It is reliable to perform gene sequencing on suspicious patients and their parents. Multidisciplinary and comprehensive treatment should be recommended to manage HP and its complications. Cholangiopancreatography and stenting is a relatively minimally invasive approach when compared with surgery and can be tried as an early intervention. Surgical procedures should be reserved for patients with complications.